Naziemne skanowanie laserowe (TLS) jako narzędzie do szacowania nadziemnej biomasy roślinności torfowiskowej = Terrestrial laser scanning (TLS) as a tool for estimating above-ground biomass of peatbog vegetation - Affek, Andrzej. Autor; Wolski, Jacek (1971– ). Autor; Solon, Jerzy (1954– ). Autor (Polska Asocjacja Ekologii Krajobrazu, 2014)
The aim of the research, conducted in the Biebrza National Park (NE Poland) was the development and initial validation of an innovative, non-invasive method for estimating the biomass of peatbog vegetation using terrestrial laser scanning (TLS) technology. Due to the large diversity of plant species on wetlands and their small-individual volumes, generating surfaces (applicable to crops) or 3D shapes (applicable to trees) does not seem to be an appropriate solution in this case. It was recognized that for the implementation of the objective pursued, the best characteristics of the LiDAR-derived point cloud is the density of the points in a given volume. Validation measurements were taken for volumes, whose projection on the ground is a square 1×1 m. An algorithm of weighting the number of points was proposed that takes into account the distance from the ground-based scanner and other scanning parameters. The results were referred to the actual weight of the dry biomass, acquired by the classical invasive method (cutting, drying, weighing). Under certain assumptions, the results of this study proved to be very promising – the coefficient of determination R2 for the linear function reached a maximum value of 0,97. However, more field data is needed for the implementation of the proposed method to the continuous monitoring system of the above-ground biomass of non-forest vegetation.
Bibliogr.
Summ. eng.
244 p. : il. (color.) ; 24 cm
Keywords: above ground biomass; LiDAR; point cloud density; Biebrza National Park